2014
DOI: 10.1016/j.acra.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

A Multiobserver Study of the Effects of Including Point-of-care Patient Photographs with Portable Radiography

Abstract: Objectives To evaluate whether the presence of facial photographs obtained at the point-of-care of portable radiography leads to increased detection of wrong-patient errors. Materials and Methods In this IRB-approved study, 166 radiograph-photograph combinations were obtained from 30 patients. Consecutive radiographs from the same patients resulted in 83 unique pairs (i.e., a new radiograph and prior, comparison radiograph) for interpretation. To simulate wrong-patient errors, mismatched pairs were generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…However, prior observer studies on integrating photographic IDs with imaging had demonstrated minimal potential impact on interpretation times [7,8,16]. Additionally, 33 % of radiologists in the current study believed that photographic IDs might be distracting.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…However, prior observer studies on integrating photographic IDs with imaging had demonstrated minimal potential impact on interpretation times [7,8,16]. Additionally, 33 % of radiologists in the current study believed that photographic IDs might be distracting.…”
Section: Discussionmentioning
confidence: 65%
“…Including patients' photos in EMR in an order verification screen prior to final signing of orders is an effective strategy for reducing the risk that medication orders will be placed in an unintended patient's EMR [14]. In radiology, observer studies demonstrated that facial photographs obtained at the time of portable chest radiographs increase detection rate of wrong-patient errors [7,8]. Other small studies (sample size of less than 50) assessing the impact of having patients' photographs available at the time of radiologists' interpretation of imaging showed no significant difference in the presence and number of clinically significant findings, when compared to studies without attached patient's photographs [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the detection rate of wrong-patient errors in portable radiography, we have developed a technology that automatically obtains point-of-care patient photographs and, using the combined radiographic Plate_ID and time stamp, ensures that the photograph and radiograph are tightly coupled in the PACS. When radiologists or other interpreting physicians view these photographs along with the corresponding radiographs in comparison with prior studies (which also contain photographs), any wrong-patient error would become obvious [4,5]. If there are no prior studies with photographs, then a comparison could be made between the photograph in the current imaging study and photographs in the patient's EMR.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, through observer studies [4,5], we demonstrated that the addition of photographs to portable radiographs could significantly increase the detection rate of simulated wrong-patient errors. Note that our scheme will not prevent wrong-patient errors at the image acquisition level; rather, it is expected to lead to increased detection of such errors at the interpretation stage, thus resulting in decreased wrong-patient radiology reports.…”
Section: Introductionmentioning
confidence: 98%